Spatial Delimitation of Coverage Focused on the Universalization of Sanitation in the Cotia River Basin – SP: Spatial Delimitation of Coverage Focused on the Universalization of Sanitation in the Cotia River Basin – SP - Toniolo, Bruno Pereira (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – To create a universalized sanitation coverage area within a hydrographic basin, including collection and treatment, using geoprocessing techniques, in accordance with the Sanitation Regulatory Framework – Law 14.026/2020.Methodology – The study area is the Cotia River Hydrographic Basin (CRHB), located in the state of São Paulo, Brazil. The method consisted of creating a coverage area representing the universalization of the Sanitation System (SS) in the BHRC, integrating data from multiple Plans of Interest (PIs) and adjustments through geoprocessing-based photointerpretation, also including the characterization of the existing SES.Originality/Relevance – The concept of infrastructure coverage for public services is rarely addressed in the literature, as it is typically a corporate matter, particularly in the context of basic sanitation and geotechnologies. Thus, exploring this subject provides novel and efficient contributions to future bibliographic research.Results – The universalized coverage area, totaling 105.31 km² (41.90% of the CRHB), displayed a complex geometry characterized by contiguity and branching, reflecting the spatial dynamics of the SS. Despite apparent fragmentation, connectivity was ensured, guaranteeing efficiency in collection and transportation for treatment. The highest densities were observed in central urban areas, while peripheral regions were identified as priorities for planned expansion. A total of 708.28 km of sewer networks need to be implemented. The study identified 42,275 water-only connections, 40,998 private households, 110 expansion areas, and 336 unserved developments, highlighting the challenges to universalizing the SS. Theoretical/Methodological Contributions – The study contributed by integrating geotechnologies and operational data into SES planning, enhancing the spatial analysis of connectivity and contiguity. The proposed methodology is replicable and serves as a foundation for future research in sanitation and urbanization.Social and Environmental Contributions – The study advanced social equity by including vulnerable urban areas and expansion zones in the sanitation coverage, reducing inequalities in access to sanitation. Environmentally, it highlighted the reduction of untreated discharges, contributing to improved water quality in the BHRC and public health.
Keywords: Geoprocessing; Sanitation